ARTERIAL HYPERTENSION WORKGROUP RESOLUTION. THE ROLE OF SARTANS IN TREATMENT OF SYSTEMIC HYPERTENSION IN THE 21ST CENTURY - A. O. Konradi; O. N. Zhdanova; O. P. Rotar; Yu. A. Karpov; V. I. Podzolkov; P. A. Lebedev; A. I. Chesnikova; D. V. Nebieridze; O. N. Miller; E. V. Solovjova; A. N. Kulikov (Российский кардиологический журнал, 2018)
.